Handbook of sport psychology - Tenenbaum, Gershon; Eklund, Robert C. (Robert Charles) 1958- (Hoboken, NJ Wiley, 2020)
In the preface to the 1st Edition of the Handbook of Sport Psychology (published by Macmillan), Singer, Murphey, and Tennant (1993) contemplated on issues relating to its structure, topical coverage, authorship, and geographic representation. They found it particularly challenging to distinguish among sport psychology, motor behavior, motor learning, motor control, and motor development while considering the contents and issues to be included in the seminal edition. Their expressed desire was also to provide coverage of research on applied issues, mainly mental interventions, which they claimed must be scientifically/evidenced based. The overall focus was aimed at providing the state of the art research in the relatively new but growing domain, while also acknowledging and highlighting conceptual and methodological issues and limitations to be addressed to facilitate further advancement. The 1st Edition of the Handbook of Sport Psyhcology consisted of 44 chapters embedded within 11 sections"--
Volume 2. Exercise, Methodologies, & Special Topics -- Part 7. Exercise as a Medicine. Physical activity promotion / Barbara E. Ainsworth, & Cheryle Der Ananian ; Chronic exercise and cognitive function: A historical view / Jennifer L. Etnier, Chang Yu Kai, & Feng-Tzu Chen ; Brain changes in response to exercise / Karen Zentgraf & Fabian Helm ; The unique contribution of physical activity to successful cognitive aging / Caterina Pesce & Claudia Voelcker-Rehage ; Exercise and multiple sclerosis: Benefits, participation rates, determinants and opportunities / Robert W. Motl, Katie L. Cederberg, Brian M. Sandroff ; The effects of exercise on anxiety and depression / Shawn M. Arent, Alan J. Walker, & Michelle A. Arent ; Physical activity and recovery from breast cancer / Meghan H. McDonough & Nichole Culos-Reed -- Part 8. Exercise engagement and effort. Progression of motivation models in exercise science: Where we have been and where we are heading? / Amanda L. Rebar and Ryan E. Rhodes ; Music-related interventions in the exercise domain: A theory-based approach / Costas I. Karageorghis ; Perceived exertion: Dynamic psychobiological model of exercise-induced fatigue / Natalia Balague, Robert Hristovski, & Sergi Garcia-Retortillo ; The automatic basis of exercise behavior: Do you like exercising? / Ralf Brand & Franziska Antoniewicz ; Habit in Exercise behavior / Amanda L. Rebar, Benjamin Gardner, & Bas Verplanken -- Part 9. Measurement & Methodologies ; Qualitative research / Brett Smith & Andrew C. Sparks ; Doing SEM bayesian-style: New opportunities for sport and exercise psychology / Cameron N. McIntosh ; Modern factor analytic techniques: Bifactor models, exploratory structural equation modeling (ESEM) and bifactor-ESEM / Alexandre J.S. Morin, Nicholas D. Myers, & Seungmin Lee ; Multilevel designs and modeling in sport and exercise psychology: Riding the current wave and looking beyond at the horizon / Patrick Gaudreau, Benjamin Schellenberg, & Alexandre Gareau ; Case study approaches in sport and exercise psychology / Stewart T. Cotterill -- Part 10. Special Topics. Performance psychology: A guiding framework for sport psychology / Markus Raab ; Gender and culture / Diane L. Gill ; Disability and sport psychology / Jeffrey Martin, Michelle Guerrero, & Erin Snapp ; Performance and appearance enhancing drug use in sports: A psychological perspective / Lambos Lazuras & Vassilis Barkoukis ; Psychological aspects in sport concussions / Semyon M. Slobounov & Alexa Walter ; Body language in sport / Philip Furley & Geoffrey Schweizer ; Athlete Burnout / Robert Eklund & J.D. DeFreese.
Includes bibliographical references and indexes.
Keywords: Sports -- Psychological aspects; Sports -- Research